Urinary Protein and Creatinine Levels of Different Haptoglobin Phenotypes among a Nigerian Pre-eclamptic Population - Odeyinka Odewusi; Emmanuella Orlu; Emmanuel Omon; Samuel Obadire; Zainab Sokunbi (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aim. Proteinuria is a major component of preeclampsia whose pathophysiology is not fully understood. The aim of this study was to determine the urinary protein and creatinine levels of different haptoglobin phenotypes among pre-eclamptic population in Ekiti State, Nigeria. Methods. A total number of 92 subjects comprising of 28 (30.43%) pregnant women diagnosed of pre-eclampsia, 34 (36.96%) pregnant women without pre-eclampsia and 30 (32.61%) non-pregnant women of child bearing age without pre-eclampsia used as control subjects. Urinary protein was determined using 25% sulphosalicylic acid, urinary creatinine was determined using Jaffe slot’s method and haptoglobin phenotypes was determined using protein electrophoresis method of polyacrylamide gel and determined using specific peroxidase staining. The results were presented in tables and charts as mean ± standard deviation. Statistical analysis was done using the Student’s t-test using SPSS software. A p-value<0.05 was considered significant. Results. The results obtained showed that in pregnant women with pre-eclampsia, BMI, SBP, DBP, urinary (mg/creatinine) were significantly higher compared to both non-pre-eclamptic pregnant women and control (p<0.05). BMI, SBP, DBP and urinary protein (mg/creatinine) was significantly higher (p<0.05) in pre-eclamptic women with the Hp 2 allele (Hp 2-2 and Hp 2-1). Hp 2 allele which has a lower scavenging effect was higher in pre-eclamptic subjects. Conclusion. In conclusion, haptoglobin 2 and increased urinary protein appears to be higher in pre-eclampsia. Therefore, this research deduced that the Hp 2 allele could be a determining factor in development of pre-eclampsia.